INTEREST RATES ON INTERBANK LOANS - Simić, Suzana (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2014)
The primary objective of the present study was to analyze the impact of the financial crisis in the euro area money market. Well regulated and efficient money market is crucial for the maintenance of liquidity. The importance of a interbank market can be seen in the crisis period when, because of the unstable economic conditions, there was a lack of fund. In this paper, first, presents the movement of daily reference rate for loans in the London interbank market, its comparison with the time indicated on the possible manipulation of the money markets. Then consider an indicator of stress in the interbank market, shown by movements in interest rates that apply in the euro zone. Special attention is paid to the role and importance of the reference rate for the Serbian dinar funds interbank market. In the last section have been analyzed and the movement of all the abovementioned interest rates on interbank loans (LIBOR, EURIBOR, BELIBOR and BEONIA) during the crisi, in order to determine how the interbank lending actually contributed to the development of the interbank market.